2016
DOI: 10.1037/abn0000172
|View full text |Cite
|
Sign up to set email alerts
|

Anticipatory reward deficits in melancholia.

Abstract: Dysfunctional reward processing has long been considered an important feature of major depressive disorder (MDD). However, depression is a heterogeneous construct and the nature of this heterogeneity may contribute to some of the inconsistent empirical findings on reward dysfunction in MDD. The current study examined one source of heterogeneity, melancholic symptoms, and its association with reward processing. In individuals with MDD (N=141) and MDD-free controls (N=113), EEG alpha asymmetry was measured durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 70 publications
(102 reference statements)
1
31
0
Order By: Relevance
“… 4 , 50 56 Some of the studies addressed specific topics such as melancholia and EEG AA. 57 It is inferred that it remains unclear whether this can be used as a surrogate marker or not. 8 , 10 , 20 , 58 Anxiety was found to be correlated with the most evident relative change in frontal alpha asymmetry in one study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 , 50 56 Some of the studies addressed specific topics such as melancholia and EEG AA. 57 It is inferred that it remains unclear whether this can be used as a surrogate marker or not. 8 , 10 , 20 , 58 Anxiety was found to be correlated with the most evident relative change in frontal alpha asymmetry in one study.…”
Section: Resultsmentioning
confidence: 99%
“…Taking a closer look at meta-analyses, 9 , 10 we found that most of the analyzed studies differ in sample age, education, gender, handedness, medication, clinical symptoms and severity, and comorbidity. EEG AA was tested as a biomarker for melancholia, 57 with unclear validity. 8 , 10 , 20 , 58 EEG AA seems to be the most robust in anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…According to the capability model of frontal EEG alpha asymmetry (Coan, Allen, & McKnight, 2006 ), the individual’s capability or typical mode to adapt to the specific demands of a certain situation is reflected in the individual’s recruitment of appropriate brain circuits in that situation, which produces characteristic asymmetry changes in the brain. These asymmetry changes, recorded in a respective context, index the individual’s capability to effectively process the specific demands and, consequently, may be indicative of traits related to psychological health and well-being (see also Allen & Reznik, 2015 ; Beeney, Levy, Gatzke-Kopp, & Hallquist, 2014 ; Cole, Zapp, Nelson, & Perez-Edgar, 2012 ; Goodman, Rietschel, Lo, Costanzo, & Hatfield, 2013 ; Liu, Sarapas, & Shankman, 2016 ; Papousek, Reiser, et al., 2013 , 2014 ; Pérez-Edgar, Kujawa, Nelson, Cole, & Zapp, 2013 ; Stewart, Coan, Towers, & Allen, 2014 ). More generally, several studies indicated functional deficits when brain circuits that are associated with these functions were inadequately activated, and that lateralized activation of specific relevant brain regions was linked to better performance on associated tasks (Davidson, Chapman, Chapman, & Henriques, 1990 ; Gur et al., 1994 , 2000 ; Gur & Reivich, 1980 ; Papousek, Murhammer, & Schulter, 2011 ; Papousek & Schulter, 2004 ; Wendt & Risberg, 1994 ).…”
Section: Introductionmentioning
confidence: 99%
“…Examples are social anxiety, greater like-ratings of objects, detached and antagonistic personality traits, melancholia, neuroticism, borderline personality disorder, and specific genetic predispositions (Davidson et al, 2000; Gable and Harmon-Jones, 2008; Harmon-Jones and Gable, 2009; Cole et al, 2012; Papousek et al, 2013, 2018; Wacker et al, 2013; Beeney et al, 2014; Uusberg et al, 2015; Liu et al, 2016). …”
Section: Introductionmentioning
confidence: 99%